THE ROLE OF EDUCATIONAL MANAGEMENT AND TRAINING ISSUES IN THE EDUCATIONAL SYSTEM - Akbarova Feruza (Scholars Digest Publishing, 2023)
The main task in educational management is to work with teachers, students, parents and society. The given descriptions of management indicate that while it means management, administrative command is fundamentally different from economic management. Through the development of educational management, it is necessary to change people's attitude to work, moral stimulation and establish friendly relations between colleagues.
Keywords: Management, management, leadership, business, fields, knowledge, enterprise, organization, office, control, administration, law, rule, plan, work.